Managing the tension: From innovation to application in health professions education. (3rd March 2020) - Tekian, Ara; Harden, Ronald M.; Cook, David A.; Steinert, Yvonne; Hunt, Daniel; Norcini, John
Abstract: Innovations in education are essential for solving problems and introducing new ways of thinking. However, implementation of these innovations must take several factors into consideration, including the context, the environment, the stakeholders, the technology needed, the cost, the pace of implementation, appropriateness, and available resources. When these factors are not balanced and considered, tensions arise. This paper describes tensions in five major educational domains, namely curriculum, instruction, assessment, accreditation/regulation, and faculty development. For each of these domains, the typical problems are described, and solutions are presented to manage the tension.